The influence of the number of recycling cycles on the thermal and physical properties of polypropylene - Cahyo Budiyantoro; Harini Sosiati; J. Wawan Joharwan (Politeknik Negeri Lhokseumawe, 2023)
Plastic recycling has become one of the approaches used to reduce environmental pollution caused by plastic waste. This study explores the influence of the number of recycling cycles on the physical and thermal properties of polypropylene (PP) plastic, which is commonly found in plastic waste. Test samples were prepared by melting waste PP in various melting cycles, including 1, 3, 5, and 10 times. The thermal and physical properties of the test samples were observed using Differential Scanning Calorimetry and its viscosity, while its microstructure was observed using a Scanning Electron Microscope. The results showed that the higher the number of recycling cycles, the lower the melting temperature (Tm) and glass transition temperature (Tg) of the PP samples. This indicates a decrease in the crystallinity properties of PP as the number of recycling cycles increases. Additionally, the flowability of PP increases with an increase in the number of recycling cycles, which can be attributed to changes in the material's structure and physical properties. The results of this study can help PP manufacturers and users optimize the recycling process and improve the quality of the resulting products. Moreover, this study also contributes positively to energy and material resource conservation as well as reducing production costs.